Adsorption of Heavy Metal Ions by Oil Palm Decanter Cake Activated Carbon - Yusoff, Mohd. Ezreeza Mohamed; Idris, Juferi; Zainal, Nahrul Hayawin; Ibrahim, Mohamad Faizal; Abd-Aziz, Suraini (UI Scholars Hub, 2019)
Adsorption processes are widely used for the removal of heavy metals from waste streams. Oil palm decanter cake (OPDC) is used as a bioadsorbent because of its compositional properties for activated carbon production; moreover, it is a readily available raw material produced in palm oil mills and is thus abundant and cheap. In this study, the OPDC was carbonized at 700 °C and activated using steam at 700 °C to produce oil palm decanter cake activated carbon (AC-OPDC). Batch adsorption experiments were carried out to compare the adsorption capacities of the raw OPDC and the AC-OPDC for heavy metals removal. The maximum adsorption capacities of AC-OPDC on Cu(II), Pb(II), and Zn(II) were found to be 45.01, 128.51, and 39.21 mg/g, respectively, which were higher than those of the raw OPDC. This study demonstrates that the AC-OPDC has the potential to be a bioadsorbent for heavy metal removal from wastewater.